Penerapan Metode Index Card Match untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Akidah Akhlak - Susilawati Susilawati; Hengki Saputra (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The application of effective teaching methods is essential for improving student learning outcomes, particularly in subjects related to character development, such as Aqidah Akhlak. One proven effective method is Index Card Match (ICM), which combines elements of collaboration and problem-solving in learning. Objective: This study aims to determine the extent to which the application of the Index Card Match (ICM) method can improve student learning outcomes in Aqidah Akhlak at MTs Ash-Shiddiqin. Method: This research uses a quantitative approach with an experimental design. The subjects of the study were eighth-grade students of MTs Ash-Shiddiqin, divided into two groups: the experimental group using the ICM method and the control group using conventional teaching methods. Data were collected through pre- and post-tests to measure the improvement in student learning outcomes. Results: The research findings indicate that the group using the Index Card Match method showed significant improvement in learning outcomes compared to the control group. This improvement was evident from the higher post-test scores in the experimental group. Conclusion: The application of the Index Card Match (ICM) method is proven to be effective in improving student learning outcomes in Aqidah Akhlak. This method can serve as a good alternative for collaborative learning and a deeper understanding of moral concepts. Contribution: This study contributes to the development of active learning methods that can be applied in Aqidah Akhlak education and provides insights for educators to use more interactive and engaging methods to enhance student learning outcomes.